POLA INFEKSI ANEKA JENIS CAPLAK ACARINA:IXODIDAE PADA BIAWAK Varanus salvator DI BEBERAPA PELOSOK DAERAH INDONESIA - Achmad Saim; Sri Hartini (The East Java Biological Society, 2001)
A total of 607 specimen (254 males, 140 femles, 92 nymph and 121 larvals) are found on 39 common water monitors from several areas in Indonesia, which are consisted of three generas (six species) of ticks. Total with discovery percentage each species of ticks on these common water-monitor are recorded 45 specimens (14%) Amblyomma helvolum , four specimens (2.6%) Aponomma komodoense, 573 specimens (71%) A. lucasi, 11 specimen (6.4%) A. sumbawaensis,eight specimens (6,4%) A. trimaculatuum, and two specimen (2.6%) Darmacentor atrosignatus. Adult of ticks and A. lucasi are found much more than other developmental stages or also its species. Its infection show of 1-4 stages or 1-2 species of ticks on each common water monitor and its parasitic index are recorded 15.6 or 1-121 of ticks on each common water-monitor. Its host, distribution and roles in ecosystem as parasites and vectors of several disease are discussed.